2003
DOI: 10.1023/a:1025861431886
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Phosphoenolpyruvate carboxylase (PEPC) was overproduced in the leaves of rice plants by introducing the intact maize C(4)-specific PEPC gene. Maize PEPC in transgenic rice leaves underwent activity regulation through protein phosphorylation in a manner similar to endogenous rice PEPC but contrary to that occurring in maize leaves, being downregulated in the light and upregulated in the dark. Compared with untransformed rice, the level of the substrate for PEPC (phosphoenolpyruvate) was slightly lower and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(22 citation statements)
references
References 25 publications
2
19
1
Order By: Relevance
“…It is likely that PEPC in darkened cucumber fruit underwent transcriptional expression regulation in a manner similar to the diurnal changes occurring in leaves of tobacco, a C 3 plant: high at the end of the night and decreasing markedly during the light period (Scheible et al , 2000). This result is also similar to previous observations that the activity of C 3 -specific PEPC in rice leaves is up-regulated in the dark (Fukayama et al , 2003). Furthermore, recent studies found that subcellular chloroplastic and cytosolic PEPCs in rice leaves have different enzymatic properties and are probably diurnally and nocturnally regulated, respectively (Fukayama et al , 2014).…”
Section: Discussionsupporting
confidence: 93%
“…It is likely that PEPC in darkened cucumber fruit underwent transcriptional expression regulation in a manner similar to the diurnal changes occurring in leaves of tobacco, a C 3 plant: high at the end of the night and decreasing markedly during the light period (Scheible et al , 2000). This result is also similar to previous observations that the activity of C 3 -specific PEPC in rice leaves is up-regulated in the dark (Fukayama et al , 2003). Furthermore, recent studies found that subcellular chloroplastic and cytosolic PEPCs in rice leaves have different enzymatic properties and are probably diurnally and nocturnally regulated, respectively (Fukayama et al , 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Compared to non-transformed, wild-type rice, transgenic rice expressing the maize PEPC gene required a higher light intensity to bring about photosynthesis saturation, had a higher photosynthetic CO 2 uptake rate and a higher carboxylation efficiency [33]. The PEPC substrate level (phosphoenolpyruvate) was slightly lower and the reaction product (oxaloacetate) was slightly higher in the transgenic rice, which suggested that the maize PEPC gene was functional in the transgenic rice lines [34]. PEPC from C 4 millet ( Seteria italica ) was introduced into Japonica rice and the transformants only showed improvements in both photosynthesis rates and yields under upland field cultivation conditions [35].…”
Section: Discussionmentioning
confidence: 99%
“…The mixture was centrifuged at 10,000× g at 4°C for 3 min, and the upper aqueous phase was used for measurements of enzyme activities. The maximal activities of enolase, PEPC and fumarase were determined as described in Lance and Guy (1992), Fukayama et al (2003) and Cooper and Beevers (1969), respectively. The maximal activities of citrate synthase and aconitase were determined as described by MacDougall and Rees (1991).…”
Section: Methodsmentioning
confidence: 99%